1982
DOI: 10.1111/j.1365-3091.1982.tb00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Bedform and stratification characteristics of some modern small‐scale washover sand bodies

Abstract: Washover sand bodies commonly develop along microtidal coastlines in beach/barrier island or spit settings. Wave runup, usually in conjunction with an abnormally high water level, may overtop the most landward berm of the beach and the foredune crest, if one exists, to produce overwash and subsequent runoff across the more landward subaerial surface. Two main elements of the resulting deposit are the washover fan and runoff channel. Newly formed, small‐scale washover deposits were examined along the Outer Bank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
59
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(75 citation statements)
references
References 20 publications
9
59
0
7
Order By: Relevance
“…However, the 1-2 m thick deposits of low-angle to planar lamination are unlikely to form subaqueously given the thickness of this deposit. In a search of the literature, 33 deposits of upper-flow-regime plane-bed lamination were found with a thickness less than a meter (Williams 1971;Shaw 1972;Schwartz 1982;Dardis 1985;Cheel and Middleton 1986;Langford and Bracken 1987;Røe 1987;Chakraborty and Bose 1992;Bal and Lewis 1994;Sohn et al 1999;Plint and Wadsworth 2003); six deposits were found with a thickness between 1 and 2 meters (Shaw 1972;Røe 1987;Bal and Lewis 1994); and three deposits were found with a thickness of 2 meters or greater (Shaw 1972;Andteron 1976;Bristow 1993).…”
Section: Alternative Interpretations For Depositional Processesmentioning
confidence: 99%
“…However, the 1-2 m thick deposits of low-angle to planar lamination are unlikely to form subaqueously given the thickness of this deposit. In a search of the literature, 33 deposits of upper-flow-regime plane-bed lamination were found with a thickness less than a meter (Williams 1971;Shaw 1972;Schwartz 1982;Dardis 1985;Cheel and Middleton 1986;Langford and Bracken 1987;Røe 1987;Chakraborty and Bose 1992;Bal and Lewis 1994;Sohn et al 1999;Plint and Wadsworth 2003); six deposits were found with a thickness between 1 and 2 meters (Shaw 1972;Røe 1987;Bal and Lewis 1994); and three deposits were found with a thickness of 2 meters or greater (Shaw 1972;Andteron 1976;Bristow 1993).…”
Section: Alternative Interpretations For Depositional Processesmentioning
confidence: 99%
“…La morfología y estructura interna de los abanicos de derrame depende de múltiples factores como la granulometría de los sedimentos, la pendiente, o bien si se depositan en un medio inundado o expuesto. Suele consistir en una estratificación horizontal o de bajo ángulo inclinada hacia tierra y estratificación cruzada (delta foreset) en la zona más distal (Hobday y Jackson, 1979;Schwartz, 1982). Cada lámina, marcada por un lag de minerales más pesados, generalmente oscuros (como ilmenita, hematite o rutilo), corresponde al paso de una ola.…”
Section: Los Eventos Catastróficos Costeros Y El Registro Sedimentariounclassified
“…Cada lámina, marcada por un lag de minerales más pesados, generalmente oscuros (como ilmenita, hematite o rutilo), corresponde al paso de una ola. Su extensión varía mucho dependiendo de la altura del cordón litoral y de la energía del oleaje, que a su vez puede estar condicionada por la pendiente de la costa (Schwartz, 1982;Jelgersma, Stire y van der Valk, 1995). El espesor de los abanicos es muy variable, pero no suele sobrepasar los 0,4 a 0,6 m y se acuñan hacia tierra o al alejarse de los levees estuarinos o canales de marea.…”
Section: Los Eventos Catastróficos Costeros Y El Registro Sedimentariounclassified
See 2 more Smart Citations